An Integrative Review of Mental Health Nurses' and Other Professionals' Experience of Associative Stigma. (9th September 2022) - Domingue, Jean-Laurent; Jager, Fiona; Lusk, Jodi; Davis, Alexandra; Ezeani, Celestina; Perkins, Meghan; Pryer, Billie
Abstract: Mental health nurses report experiencing stigmatization both from within and outside the profession, and associative stigma provides one way to explore that experience. To better understand the current state of the literature on mental health care professionals' experiences of associative stigma, and particularly on nurses' experience of this phenomenon, an integrative review of the literature on the subject was conducted. The results detail factors associated with associative stigma, the effects of associative stigma on nurses and caregivers of persons with mental illnesses, and the quantification of associative stigma. This article concludes by discussing implications for nursing practice, education, and research.